Are the school version of the assessment of motor and process skills measures valid for German-speaking children?. (23rd February 2019) - Kaelin, Vera C.; van Hartingsveldt, Margo; Gantschnig, Brigitte E.; Fisher, Anne G.
Abstract: Background: There are no validated assessment tools for evaluating quality of schoolwork task performance of children living in German-speaking Europe (GSE). Objective: To determine whether the international age-normative means of the School Version of the Assessment of Motor and Process Skills (School AMPS) are valid for use in GSE. Methods: The participants were 159 typically-developing children, 3-12 years, from GSE. We examined the proportions of School AMPS measures falling within ±2 standard deviation ( SD ) of the international age-normative means, and evaluated for significant group differences ( p  < 0.05) in mean School AMPS measures between the GSE sample and the international age-normative sample using one-sample Z tests. When significant mean differences were found, we evaluated if the differences were clinically meaningful. Results: At least 95% of the GSE School AMPS measures fell within ±2 SD of the international age-normative means for the School AMPS. The only significant mean differences were for 6- ( p  < 0.01) and 8-year-olds ( p  = 0.02), and only the 6-year-old school process mean difference was clinically meaningful. Conclusions: Because the only identified clinically meaningful difference was associated with likely scoring error of one rater, the international age-normative means of the School AMPS appear to be valid for use with children in GSE.